Aurintricarboxylic Acid Attenuates Intimal Thickening after Balloon Injury of the Rabbit Aorta - Waissbluth, Alvaro; Ghigliotti, Giorgio; Abendschein, Dana R.; Eisenberg, Paul R.; Schwartz, David (Thrombosis and Haemostasis, 2002)
Injury to the arterial wall initiates a cascade of events including platelet deposition and an increase in procoagulant activity of the vessel wall that is associated with intimal thickening and vascular wall remodeling. This study was designed to characterize the effects of aurintricarboxylic acid (ATA), an inhibitor of von Willebrand factor function, on vascular procoagulant activity and the development of intimal thickening after balloon-induced injury to the rabbit aorta.Treatment with ATA, aspirin, or the combination of agents at doses that attenuated platelet aggregation decreased platelet deposition and procoagulant activity bound to the vessel wall after injury. Treatment with ATA reduced the intimal thickening observed 2 weeks after injury. Surprisingly, aspirin treatment had no effect on intimal thickening. These data indicate that inhibition of platelet deposition, while it is able to attenuate local thrombin elaboration, is not alone sufficient to attenuate subsequent intimal thickening that occurs in response to arterial injury.
Keywords: Arterial injury; neointima; aurintricarboxylic acid; rabbit